An experimental investigation into the shock response of a compact wire rope isolator in its axial direction. (1st July 2022) - Ledezma-Ramírez, D.F.; Tapia-González, P.E.; Brennan, M.J.; Paupitz Gonçalves, P.J.
Highlights: A wire rope isolator is experimentally characterized determin finding the nonlinear stiffness and damping by static and cyclic loading. Shock response is calculated considering nonlinear stiffness and damping fitted from experimental data. Shock response is evaluated experimentally for impacts of different duration and amplitudes, finding improved isolation for high rate impacts. Experimental validation is presented using the nonlinear stiffness and damping model considering the actual impacts experimentally recorded as inputs for the numerical simulations. Shock response of the wire rope isolators can be reasonably predicted using a nonlinear cubic 5th order polynomial stiffness and velocity  n -th power damping model. Abstract: The use of wire rope isolators (WRIs) for vibration and shock response attenuation is extensive, as these isolators offer a high level of energy storage due to deflection in different directions, combined with high damping due to dry friction. As a result, they are marketed by manufacturers as excellent shock isolators. However, technical information regarding the shock response of these devices is limited, focusing on static properties and vibration isolation, whilst most of the scientific studies aim at the modelling and characterisation of properties. This study presents novel results from experiments involving both static and dynamic testing. Important information concerning the stiffness and damping characteristics are experimentally determined, as well as their behaviour under shock inputs of varying severity and duration for different payloads. It is shown that a WRI under low-level shock loads can be modelled crudely as a low dynamic stiffness system with a 5th order polynomial and n th power velocity damping. Although this approach is limited in predicting high input shocks and the dynamics of the hysteretic system under periodic loads compared to other models, it provides a simpler approach to predict the shock response of a WRI for engineering purposes.